2021
DOI: 10.3389/fphys.2021.653045
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Increased Systemic ACE2 Activity Is Associated With an Increased Inflammatory Response in Smokers With COVID-19

Abstract: Background: Tobacco smoking is known to be involved in the pathogenesis of several cardiopulmonary diseases. Additionally, smokers are highly susceptible to infectious agents due to weakened immunity. However, the progression of lung injury based on SARS-CoV-2-mediated COVID-19 pathogenesis amongst smokers and those with pre-existing pulmonary diseases is not known. We determined the systemic levels and activity of COVID-19 associated proteins, cytokine/chemokines, and lipid mediators (lipidomics) amongst COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
2
9
1
Order By: Relevance
“…However, longitudinal evaluation of soluble ACE2 in patient-matched samples showed a significant decrease, indicating that viral infection is significantly affecting ACE2 function. Indeed, soluble ACE2 measured in plasma showed a decrease over time, in line with previous reports [ 14 , 35 , 36 ]. Overall, we demonstrate that SARS-CoV-2 infection induces shedding of ACE2 from cell membranes, leading to increased levels of the soluble active form of ACE2 in situ; however, it is also found later on in plasma, when the infection has spread systemically.…”
Section: Discussionsupporting
confidence: 91%
“…However, longitudinal evaluation of soluble ACE2 in patient-matched samples showed a significant decrease, indicating that viral infection is significantly affecting ACE2 function. Indeed, soluble ACE2 measured in plasma showed a decrease over time, in line with previous reports [ 14 , 35 , 36 ]. Overall, we demonstrate that SARS-CoV-2 infection induces shedding of ACE2 from cell membranes, leading to increased levels of the soluble active form of ACE2 in situ; however, it is also found later on in plasma, when the infection has spread systemically.…”
Section: Discussionsupporting
confidence: 91%
“…Of interest, as in our previous (11) and present work, researchers in Canada reported an upward trajectory of soluble ACE2 at 7-day sampling (from baseline) that was independently associated with increased mortality risk among their 242 patients with COVID-19 (29). A relationship among ACE2, disease severity, and mortality emerged in yet another analysis, this one from Hungary, of 176 patients with COVID-19 (30), and ve additional studies have demonstrated elevated to highly elevated ACE2 levels in COVID-19 (31)(32)(33)(34)(35). Three other studies found no ACE2 elevation in COVID-19 (36-38), possibly because the included patients were less severely affected and/or ACE2 was measured only at the beginning of the disease course.…”
Section: Ace-ssupporting
confidence: 55%
“…Evidence suggests that perturbations in arachidonic acid pathways could lead to an imbalance between the pro-inflammatory metabolites of arachidonic acid including mid-chain hydroxyeicosatetraenoic acid (HETEs) and terminal HETE (20-HETE) [31]. Previous work by our group demonstrated increased levels of 15-HETE and 20-HETE in the serum of COVID-19-positive patients [32]. The elevated levels of arachidonic acid in the patient sera from COVID-19-positive individual further points towards the crucial nature of this metabolic pathway in the pathophysiology of COVID-19.…”
Section: Discussionmentioning
confidence: 73%
“…We obtained patient sera from COVID-19-positive (CoV) and COVID-19-recovered (Rec) subjects from BioIVT (Westbury, NY, USA) [32]. The de-identified samples did not require any local IRB requirements or consent forms under 45 CFR 46.102.…”
Section: Human Subjectsmentioning
confidence: 99%